Five‐to‐Seven Carbon Glycols Severely Impair Bioenergetics and Metabolism of Aggressive Lung Cancer Cells. Issue 9 (8th September 2022) - Stefanello, Sílvio Terra; Mizdal, Caren Rigon; Azzam, Ihab; Döhlinger, Lilly; Oeckinghaus, Andrea; Shahin, Victor
Abstract : Lung Cancer Metabolic reprogramming is a hallmark of metastatic lung cancer cells (A549_3R). In article number 2200050, Victor Shahin and co‐workers establish that 5‐7 carbon glycols reduce the A549_3R ATP production by interfering with LDH and mitochondria. The cover image reveals a decline in mitochondrial membrane potential of A549_3R when exposed to 1, 6‐HD.